Water Exposure is a Common Risk Behavior Among Soft and Gas-Permeable Contact Lens Wearers. Issue 8 (August 2017) - Zimmerman, Aaron B.; Richdale, Kathryn; Mitchell, Gladys Lynn; Kinoshita, Beth T.; Lam, Dawn Y.; Wagner, Heidi; Sorbara, Luigina; Chalmers, Robin L.; Collier, Sarah A.; Cope, Jennifer R.; Rao, Maya M.; Beach, Michael J.; et al.
Abstract : Purpose: To understand soft contact lens (SCL) and gas-permeable (GP) lens wearers' behaviors and knowledge regarding exposure of lenses to water. Methods: The Contact Lens Risk Survey (CLRS) and health behavior questions were completed online by a convenience sample of 1056 SCL and 85 GP lens wearers aged 20 to 76 years. Participants were asked about exposing their lenses to water and their understanding of risks associated with these behaviors. Chi-square analyses examined relationships between patient behaviors and perceptions. Results: GP lens wearers were more likely than SCL wearers to ever rinse or store lenses in water (rinsing: 91% GP, 31% SCL, P < 0.001; storing: 33% GP, 15% SCL P < 0.001). Among SCL wearers, men were more likely to store (24% vs. 13%, P = 0.003) or rinse (41% vs. 29%, P = 0.012) their lenses in water. Showering while wearing lenses was more common in SCL wearers (86%) than GP lens wearers (67%) ( P < 0.0001). Swimming while wearing lenses was reported by 62% of SCL wearers and 48% of GP lens wearers ( P = 0.027). Wearers who rinsed (SCL; P < 0.0001, GP; P = 0.11) or stored lenses in water (SCL; P < 0.0001, GP P = 0.007) reported that this behavior had little or no effect on their infection risk, compared with those who did not. Both SCL ( P < 0.0001) and GP lens wearers ( P < 0.0001) perceived that distilled water was safer than tap water for storing or rinsing lenses. Conclusions: Despite previously published evidence of Acanthamoeba keratitis' association with water exposure, most SCL, and nearly all GP lens wearers, regularly expose their lenses to water, with many unaware of the risk.